2017
DOI: 10.1515/eng-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polymer fibers on rheological properties of cement mortars

Abstract: Abstract:The reinforcing effect of fibers in cement composites often results in the improvement of the brittle nature of cementitious materials. But the decrease in the workability of fresh concrete is often the disadvantage of fibers addition. Conventional single-point workability tests cannot characterize workability of concrete in terms of fundamental rheological parameters. To this end, this paper describes an investigation of the influence of synthetic fiber additions (fiber length in the range 12-50 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 28 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Malaszkiewicz et al [ 49 ] selected three polymer fibers with a length of 12 mm to 50 mm and a volume fraction of 0% to 4% to conduct mortar fluidity and setting time experiments. According to the test results, it was found that fiber type and fiber length had no significant effect on the yield strength of mortars.…”
Section: Effect Of Fiber On 3dpm Workabilitymentioning
confidence: 99%
“…Malaszkiewicz et al [ 49 ] selected three polymer fibers with a length of 12 mm to 50 mm and a volume fraction of 0% to 4% to conduct mortar fluidity and setting time experiments. According to the test results, it was found that fiber type and fiber length had no significant effect on the yield strength of mortars.…”
Section: Effect Of Fiber On 3dpm Workabilitymentioning
confidence: 99%